Accounting Prudence Pada Perusahaan Bernotasi Khusus - Nilam Kelama Odang; Maryam Monika Rangkuti (Mahesa Research Center, 2023)
Financial statements prepared using the accrual basis give rise to accounting prudence. The main factor that causes prudence to arise is conditions full of uncertainty, which creates caution, such as that caused by the Covid-19 pandemic. This study aims to analyze differences in accounting production before and during the Covid-19 pandemic for companies with special notations (2018 – 2021). The method used in this study is a quantitative method using the Paired T-Test for data analysis. The results of the study show that there is no significant difference between accounting prudence at companies with special notations before and during the Covid-19 pandemic.